INFLUENCE OF CYANIDE ON REMOVAL OF COPPER ION FROM THE SOLUTION BY PHOTOCATALYTIC REDUCTION METHOD WITH TiO2 SUSPENSION - Endang Tri Wahyuni; Mudasir Mudasir; Tania Avia Gusman (Universitas Gadjah Mada, 2010)
The removal of Cu(II) by photoreduction method using TiO2 photocatalyst in the presence of CN- is reported. Photoreduction was carried by batch technique using UV lamp with 290-350 nm of wavelength. The research results indicate that the present of CN- ion gives different effects on the photoreduction effectiveness depends on the mole ratio of both ions. The addition of CN- less than 2 moles for each mole of Cu (II) ion can improve the photoreduction, and the photoreduction sharply goes down into very low degree when the mole number of CN- is increased up to 4, and by further enlarging the mole number into 6, the photoreduction degree remains constant. Furthermore, increasing solution pH generally leads to a decrease in the photoreduction. In the solution with pH 1, the maximal photoreduction degree is reached, while increasing pH from 1 to 9 has declined the photoreduction, and the photoreduction is totally inhibited at pH higher than 9. The effect of the solution pH is related with the speciation of Cu (II), CN- and TiO2 in the solution.